ḤIJĀB DAN JILBAB PERSPEKTIF ASMA BARLAS DAN POSISINYA DALAM TIPOLOGI TAFSIR KONTEMPORER SAHIRON SYAMSUDDIN - Muhammad Imdad Ilhami Khalil; A. Halil Thahir (Institut Agama Islam Negeri (IAIN) Keiri, 2021)
Abstract Up to now, the research on ḥijāb and jilbab is still a debatable and relevant topic for further discussion. One of the figures who took part in the ḥijāb and jilbab problem is Asma Barlas. He criticized the understanding of Muslims, especially the interpretation product of conservatives scholars, who reduced the meaning of the ḥijāb to the obligation to wear a ḥijāb. According to her, the obligation to wear the ḥijāb by wearing the jilbab is still influenced by the patriarchal and misogynistic mindset of the jāhiliyyah community. This article aims to explain the construction of Asma Barlas' thought, especially in the issue of ḥijāb and jilbab. Then, this article will also try to place the thoughts of Asma Barlas in the Typology of Contemporary Interpretation of Thought initiated by Sahiron Syamsuddin. The categorization of contemporary commentary thought initiated by Sahiron Syamsuddin makes it easier for later researchers to identify the basic construction of an interpreter thoughts of the Qur'an.